Evidence of precursor orthorhombic domains well above the electronic nematic transition temperature in Sr(Fe1-xCox)2As2 - Kaneko, Ulisses; Piva, Mario; Ramos de Jesus, Camilo Bruno; Saleta, Martin Eduardo; Urbano, Ricardo; Pagliuso, Pascoal G.; Granado, Eduardo (IOP Publishing, 2019)
Fil: Kaneko, Ulisses. Laboratorio Nacional de Luz Sincrotron;; Brasil